VALIDITY OF SUPPLEMENTARY TEACHING MATERIALS ON BUFFER SOLUTION TO TRAIN ARGUMENTATION SKILLS - Noviyana, Dyah Kirani; Suyono, Suyono (Program Studi Pendidikan Fisika, FITK, UNSIQ, 2024)
The purpose of this research is to produce supplementary teaching materials on buffer solution materials that are valid in practicing argumentation skills. This research is a type of development research that focuses on developing products for learning using the ADDIE model which is limited to the development stage. The instrument used in this research is a validation sheet consisting of content and construct validity. The target of the research is supplementary teaching materials in practicing argumentation skills on buffer solutions. The teaching materials were assessed by 3 validators, namely experts in chemistry learning. The results of the assessment through this validation sheet obtained a mode of 4 which was declared valid. Based on this assessment, it can be concluded that the supplementary teaching materials on buffer solution material are valid in supporting argumentation skills training.